Daytime and nighttime color appearance of pigmented asphalt surface treatments. (20th May 2019) - Autelitano, Federico; Giuliani, Felice
Graphical abstract: Highlights: Direct measurement of the daytime chromaticity coordinates of pigmented slurry seals. Proposal of a rational methodology for evaluating the nighttime chromatic perception of pavements. Influence of outdoor light sources on pavement color appearance. Abstract: The use of distinctive and decorative road colored pavements intended for motorized traffic, cyclists and pedestrians have dramatically increased worldwide. They could take the form of overlay, when the colored material is placed on top of the pavement, or embedded, when the colored material is mixed directly into the pavement, exploiting the natural chromatic properties of stone aggregates or powder pigments. Colored pavements are not generally considered as signs or road markings and therefore, no having a legal status, are not subjected to chromaticity requirements. Thus, the paper proposed a rational methodology for the chromatic characterization of colored asphalt pavements, considering different thin cold pigmented high friction road surface treatments, i.e. pigmented slurry seals (red, green and blue), prepared with a clear synthetic emulsion. The experimental procedure had the ambition to predict the chromatic aspect of these pavements, based on direct instrumental measurements of chromaticity coordinates on laboratory scale samples, for several pigment contents in daytime and nighttime. Experimental results testified how the correct transfer and application of a particular color to a road pavement, which often perform traffic functions, cannot be separated from an integrated design between pavement materials selection and road lighting project.